Production of interleukin-6 by human and murine mononuclear leukocytes stimulated with Plasmodium antigens is enhanced by pentoxifylline, and tumor necrosis factor secretion is reduced. - Prada, J (1993)
When pentoxifylline was present during stimulation of human mononuclear leukocytes with Plasmodium falciparum exogenous antigens, an increase in interleukin-6 production was observed simultaneously with a reduction of tumor necrosis factor secretion. Similar results were obtained in murine macrophages stimulated with P. vinckei antigens. This indicates the independence of interleukin-6 and tumor necrosis factor secretion in response to malaria antigens.